(untitled) (Journal of the College of Basic Education, 2022)
The current research aims to: 1- Know the role of artistic activities in developing aesthetic preference. 2- Measuring the effectiveness of artistic activities in developing the aesthetic preference of middle school students. As for the research methodology, the researcher followed the experimental approach to designing her research procedures, as it is the most appropriate scientific method to achieve the goal of the research. To (54) middle school. A random sample of second-grade students in the middle school (Umm Salamah for girls) was selected, as the choice was made on a division of (32) students who were identified within one group (experimental). The research came out with a set of conclusions, the most important of which are: 1- The artistic activities contributed to developing the aesthetic preference of the experimental sample students as it is a purposeful and self-directed and collective process by the School of Art Education. 2- It appears through the practice of artistic activities in the school corridors that contribute to the development of the students’ technical skills and its reflection on their characteristics at this stage, which led to the achievement of the educational goals specified for this purpose.